A cor da cobertura plástica do solo favorece o crescimento vegetativo, a produção e a qualidade de minitomates? - Silva, Valdiney José da (2018)
Covering the soil surface with colored plastics (mulching) modifies the microclimate and can increase the crops development, production and quality. However, the effects can differ among crops, location and growing season. The aim of this work was to highlight the influences of the colored plastics upon several cultures conduced in different site and season, besides evaluating the growth, production and solid soluble content of mini tomatoes tilled on three plastic colors in field condition. Two experiments were carried out at different times, one during the summer/fall (16 Jan. – 30 Apr.) and the other during the winter/spring (23 Aug. – 29 Nov.) of 2017. The experiments were conducted in randomized blocks, in a 2 x 4 factorial schemes, with four replications. The first factor was two cultivars of mini tomatoes, one with determined growth habit and the other, indeterminate. The other factor was three colors of plastic cover (black, black/silver and black/white) and the control without covering the soil surface. The plots were composed by 14 plants conducted in double rows spaced of 0.3 x 0.7 x 1.3 m, being evaluated the 10 central plants. The soil temperatures under the covers were recorded at hourly intervals using a data logger connected to a multiplexer, by using a copper-constantan thermocouple cable from each plot, installed at 5.0 cm depth. The soil temperatures underground covers, mean stem diameter, plant height, flowering mid time, productivity and the fruit soluble solids content were analyzed. All the results were submitted to variance analysis by F test, and if significant, the averages were compared by Tukey test at 0.05 of significance. The review shows that the choice of plastic coloration more fitting for growth and productivity depends of the crop and the climatic conditions of the site or growing season. In both experiments, higher temperature was recorded in the soil covered with black and black/silver colors. In the summer/autumn crop, higher yield was obtained with the determined growth cultivar using the black/silver color, but no effect of the color or the presence of the plastic cover was not found in the soluble solids content. For the winter/spring crop the two cultivars, showed greater heights on the black/silver, but higher productivity and soluble solids content with the black color. It is suggested to evaluate other colors of plastic cover and new mini tomatoes materials cultivated under field conditions.